NHT Type Assisted Cooperative Learning with Multimedia Referring to Cognitive Load Theory to Improve Learning Outcomes - Yul Pendri (Universitas Negeri Malang, 2015)
Pembelajaran Kooperatif Tipe NHT Berbantuan Multimedia Mengacu pada Cognitive Load Theory untuk Meningkatkan Hasil Belajar Abstract: This study aims to determine the application of cooperative learning Numbered Head To-gether (NHT) with multimedia-assisted cognitive load refers to the theory that can improve mathematics learning outcomes. The study design was a class action research conducted by 2 cycles. Each cycle consists of 3 sessions or 6 x 35 minutes. Research subjects fifth grade students of SDN 124/IV Jambi with 32 students. Implementation cycles through three stages, namely the initial activity/apperception, core activities include; (1) numbered, (2) questioning, (3) heads together, (4) answering, and closing activities. Each stage accompanied by a power point slide show as a supporting medium to convey information. The results showed that the students are able to participate actively in the learning, increasing curiosity, build self-confidence, social interaction among students increased, the emergence of a sense of responsibility to the individual, as well as good cooperation in the understanding of knowledge. Key Words: cooperative learning numbered head together, multimedia, cognitive load theory, learning outcomes Abstrak: Penelitian ini bertujuan untuk mengetahui penerapan pembelajaran kooperatif numbered head together (NHT) dengan berbantuan multimedia mengacu pada cognitive load theory yang dapat meningkatkan hasil belajar matematika. Penelitian menggunakan rancangan penelitian tindakan kelas (PTK) yang dilaksanakan sebanyak 2 siklus. Setiap siklus terdiri dari 3 kali pertemuan atau 6 x 35 menit. Subjek penelitian siswa kelas V SDN 124/IV Jambi yang berjumlah 32 siswa. Pelaksanaan siklus melalui tiga tahapan, yakni kegiatan awal/ apersepsi, kegiatan inti meliputi; (1) numbered, (2) questioning, (3) heads together, (4) answering, dan kegiatan penutup. Setiap tahapan diiringi tampilan slide power point sebagai media pendukung menyampaikan informasi. Hasil penelitian menunjukkan bahwa siswa mampu berpartisipasi aktif dalam pembelajaran, meningkatnya rasa ingin tahu, membangun kepercayaan diri, interaksi sosial antar siswa meningkat, timbulnya rasa tanggungjawab terhadap individu, serta terjalinnya kerjasama yang baik dalam memahami pengetahuan.  Kata kunci: pembelajaran kooperatif numbered head together, multimedia, cognitive load theory, hasil belajar